Searching for Caleb - Tyler, Anne (New York Fawcett Books, 1996)
Duncan Peck is a restless man with a fascination for randomness which translates into constant moves for his family. his wife Justine, is a highly accessible fortune teller who has problems piecing together fragments of the past. her grandfather, Danial, is on a quest of his own, longing to find the brother who simply walked down the driveway one spring day in 1912 with nothing more than fiddle in his hand, never to return. All three are taking journeys that lead back to the family's deepest roots... to a place where rebellion and acceptance have the haunting power to merge into one
American corner
11
Keywords: English stories